Identification of a novel PPARβ/δ/miR‐21‐3p axis in UV‐induced skin inflammation. Issue 8 (1st June 2016) - Degueurce, Gwendoline; D'Errico, Ilenia; Pich, Christine; Ibberson, Mark; Schütz, Frédéric; Montagner, Alexandra; Sgandurra, Marie; Mury, Lionel; Jafari, Paris; Boda, Akash; Meunier, Julien; Rezzonico, Roger; et al.
Abstract: Although excessive exposure to UV is widely recognized as a major factor leading to skin perturbations and cancer, the complex mechanisms underlying inflammatory skin disorders resulting from UV exposure remain incompletely characterized. The nuclear hormone receptor PPARβ/δ is known to control mouse cutaneous repair and UV‐induced skin cancer development. Here, we describe a novel PPARβ/δ‐dependent molecular cascade involving TGFβ1 and miR‐21‐3p, which is activated in the epidermis in response to UV exposure. We establish that the passenger miRNA miR‐21‐3p, that we identify as a novel UV‐induced miRNA in the epidermis, plays a pro‐inflammatory function in keratinocytes and that its high level of expression in human skin is associated with psoriasis and squamous cell carcinomas. Finally, we provide evidence that inhibition of miR‐21‐3p reduces UV‐induced cutaneous inflammation in ex vivo human skin biopsies, thereby underlining the clinical relevance of miRNA‐based topical therapies for cutaneous disorders. Synopsis: The skin response to UV as well as psoriasis or squamous cell carcinoma are complex pathophysiological situations. The microRNA miR‐21‐3p is shown to be a novel target of PPARβ/δ and TGFβ that controls inflammation in mouse and human epidermis. miR‐21‐3p is induced by UV irradiation in mouse and human epidermis. PPARβ/δ and TGFβ activation is required for UV‐induced miR‐21‐3p upregulation in the epidermis. Elevated miR‐21‐3p level correlates with psoriasis and squamous cell carcinoma in human skin. Inhibition of miR‐21‐3p reduces UV‐induced inflammation in human skin ex vivo . Abstract : The skin response to UV as well as psoriasis or squamous cell carcinoma are complex pathophysiological situations. The microRNA miR‐21‐3p is shown to be a novel target of PPARβ/δ and TGFβ that controls inflammation in mouse and human epidermis.